Effects of ultrasound‑guided pericapsular nerve group block in combination with laryngeal mask airway on anesthesia, postoperative analgesia, and recovery of elderly patients with femoral neck fracture undergoing closed reduction and internal fixation - Rongen Qiu; Yunping Lan; Gang Liu; Ruifeng Zeng (Videosurgery and Other Miniinvasive Techniques)
Introduction: Femoral neck fracture (FNF) frequently occurs in the elderly. FNF is usually treated surgically, but patients often have comorbidities, which make the surgery complicated and increase the intraoperative risk.